Therapeutic termination of pregnancy (TTOP) in patients with medical disorders - Kaluarachchi, A; Gunasekara, J.M.W; Mahesh, W (My University)
At present many patirnts who have medical conditions where the pregnancy is contra indicated become pregnant. In tins sanation TTOP becomes necessary to avoid maternal mortality and morbidity. This study was performed to identify the indications for TTOP and the outcome of these mothers who were referred to the Department of. Obstetrics and Gynaecology, Faculty of Medicine, Colombo from February 2001 to October 2009.